Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Clinical significance of hyper-IgA in a paediatric laboratory series. - Copetti, Valentina; Pastore, Serena; De Pieri, Carlo; Radillo, Oriano; Taddio, Andrea; Ventura, Alessandro; Tommasini, Alberto (Arch Dis Child, 2014)
The causes of extremely elevated IgA, whether isolated or associated with an increase in other classes of immunoglobulin, are poorly defined in paediatrics. We reviewed the diagnostic significance of very high IgA levels (greater than 3 SD above the mean for age) in a cohort of patients referred to a tertiary care children's hospital. Hyper-IgA was found in 91 of 6364 subjects (1.4%) and in 68 cases was not associated with an increased IgG and/or IgM level. Most subjects with hyper-IgA (73.5%) had a severe immune defect, a chronic rheumatic disease or inflammatory bowel disease, while these conditions were very rare in a control group with normal IgA values (8%). Although our results may in part reflect the experience of a tertiary care centre, we suggest that hyper-IgA in children should always arouse suspicion of a serious disease.
Keywords: Adolescent; Child; Child, Preschool; Female; Hospitals, Pediatric; Humans; Hypergammaglobulinemia; Immunoglobulin A; Infant; Italy; Male; Tertiary Care Centers

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation